Reconstruction of full high‐resolution HSQC using signal split in aliased spectra. (20th August 2015) - Foroozandeh, Mohammadali; Jeannerat, Damien; Giraudeau, Patrick
Abstract Resolution enhancement is a long‐sought goal in NMR spectroscopy. In conventional multidimensional NMR experiments, such as the 1H‐13C HSQC, the resolution in the indirect dimensions is typically 100 times lower as in 1D spectra because it is limited by the experimental time. Reducing the spectral window can significantly increase the resolution but at the cost of ambiguities in frequencies as a result of spectral aliasing. Fortunately, this information is not completely lost and can be retrieved using methods in which chemical shifts are encoded in the aliased spectra and decoded after processing to reconstruct high‐resolution 1H‐13C HSQC spectrum with full spectral width and a resolution similar to that of 1D spectra. We applied a new reconstruction method, RHUMBA (reconstruction of high‐resolution using multiplet built on aliased spectra), to spectra obtained from the differential evolution for non‐ambiguous aliasing‐HSQC and the new AMNA (additional modulation for non‐ambiguous aliasing)‐HSQC experiments. The reconstructed spectra significantly facilitate both manual and automated spectral analyses and structure elucidation based on heteronuclear 2D experiments. The resolution is enhanced by two orders of magnitudes without the usual complications due to spectral aliasing. Copyright © 2015 John Wiley & Sons, Ltd.